Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 9.3

Ex 9.3, 1
Important

Ex 9.3, 2

Ex 9.3, 3

Ex 9.3, 4 Important

Ex 9.3, 5

Ex 9.3, 6

Ex 9.3, 7 Important

Ex 9.3, 8

Ex 9.3, 9 Important

Ex 9.3, 10 Important

Ex 9.3, 11 Important

Ex 9.3, 12 You are here

Ex 9.3, 13

Ex 9.3, 14

Ex 9.3, 15 Important

Ex 9.3, 16

Ex 9.3, 17 Important

Ex 9.3, 18

Ex 9.3, 19 Important

Ex 9.3, 20 Important

Ex 9.3, 21

Ex 9.3, 22 Important

Ex 9.3, 23 (MCQ)

Last updated at Aug. 11, 2023 by Teachoo

Ex 9.3, 12 Find a particular solution satisfying the given condition : 𝑥(𝑥^2−1) 𝑑𝑦/𝑑𝑥=1;𝑦=0 When 𝑥=2 𝑥(𝑥^2−1) dy = dx dy = 𝒅𝒙/(𝒙(𝒙𝟐 − 𝟏)) Integrating both sides. ∫1▒𝑑𝑦 = ∫1▒𝑑𝑥/(𝑥(𝑥2 − 1)) 𝒚 = ∫1▒𝒅𝒙/(𝒙(𝒙 + 𝟏)(𝒙 − 𝟏)) We can write integrand as 𝟏/(𝒙(𝒙 + 𝟏)(𝒙 − 𝟏)) = 𝑨/𝒙 + 𝒃/(𝒙 + 𝟏) + 𝒄/(𝒙 − 𝟏) By canceling the denominators. 1 = A (x − 1) (x + 1) B x (x − 1) + C x (x + 1) Putting x = 0 1 = A (0 − 1) (0 + 1) + B.0. (0 − 1) + C.0. (0 + 1) 1 = A (−1) (1) + B.0 + C.0 1 = − A A = −1 Similarly putting x = −1 1 = A (−1 − 1) (−1 + 1) + B (−1) (−1 − 1) + C(−1)(−1 + 1) 1 = A (−2) (0) + B (−1) (−2) + C (−1) (0) 1 = 0 + 2B + 0 2B = 1 B = 𝟏/𝟐 Similarly putting x = 1 1 = A(1 − 1) (1 + 1) + B.1(1 − 1) + C(1)(1 + 1) 1 = A (0) (2) + B.1.0 + C.2 2C = 1 C = 𝟏/𝟐 Therefore, 𝟏/(𝒙(𝒙 + 𝟏)(𝒙 − 𝟏)) = (−𝟏)/𝒙 + 𝟏/(𝟐(𝒙 + 𝟏)) + 𝟏/(𝟐(𝒙 − 𝟏)) Now, From (1) y = ∫1▒1/(𝑥(𝑥 + 1)(𝑥 − 1)) dx = − ∫1▒𝟏/𝒙 + dx + 𝟏/𝟐 ∫1▒𝒅𝒙/(𝒙 + 𝟏) + 𝟏/𝟐 ∫1▒𝒅𝒙/(𝒙 − 𝟏) = log |𝒙|+ 𝟏/𝟐 log |𝒙+𝟏| + 𝟏/𝟐 log |𝒙−𝟏|+𝒄 = (−2)/2 log|𝑥| + 𝟏/𝟐 log |𝒙+𝟏|+ 𝟏/𝟐 log |𝒙−𝟏|+𝑐 = 1/2 [−2 log〖|𝑥|−2+𝐥𝐨𝐠|(𝒙+𝟏)(𝒙−𝟏)| 〗 ]+𝑐 = 1/2 [log〖𝑥^(−2)+log|(𝑥+1)(𝑥−1)| 〗 ]+𝑐 = 1/2 [log|𝑥^(−2) (𝑥^2−1)| ]+𝑐 = 𝟏/𝟐 log |(𝒙^𝟐 − 𝟏)/𝒙^𝟐 |+𝒄 Given that x = 2, y = 0 Substituting values in (1) we get 0 = 1/2 " log " |(2^2−1)/2^2 |" + C" 0 = 1/2 " log " 3/4 " + C" C = −𝟏/𝟐 " log " 𝟑/𝟒 Putting value of c in (1), y = 𝟏/𝟐 log |(𝒙^𝟐 − 𝟏)/𝒙^𝟐 | − 𝟏/𝟐 log 𝟑/𝟒